Verification of a foreign business partner based on examples of chosen public open-source registers in the context of due diligence - Ćwiąkała-Małys, Anna; Piotrowska, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Verification of foreign business partners that are registered in European Union is possible through integrated commercial register of member states. The community trade register can be accessed via free service on the “e-Justice” website. The portals also allows one to verify the insolvency and bankruptcy register or the register of actual beneficial owners. The scope of presented information is determined by internal law of each member state. Thus there is a lack of uniformity in presenting business information regarding registered entities in individual countries. This article presents and compares internal solutions in access to public information on companies in three countries from the former Easter Block, i.e. so-called post-transformation countries, that is the Czech Republic, the Slovak Republic and Bulgaria.
Keywords: public information databases; commercial register; insolvency register; beneficial ownership register